Pulsed Electromagnetic Fields Stimulate HIF-1α-Independent VEGF Release in 1321N1 Human Astrocytes Protecting Neuron-Like SH-SY5Y Cells from Oxygen-Glucose Deprivation - Fabrizio Vincenzi (International Journal of Molecular Sciences, 2020)
Pulsed electromagnetic fields (PEMFs) are emerging as an innovative, non-invasive therapeutic option in different pathological conditions of the central nervous system, including cerebral ischemia. This study aimed to investigate the mechanism of action of PEMFs in an in vitro model of human astrocytes, which play a key role in the events that occur following ischemia. 1321N1 cells were exposed to PEMFs or hypoxic conditions and the release of relevant neurotrophic and angiogenic factors, such as VEGF, EPO, and TGF-β1, was evaluated by means of ELISA or AlphaLISA assays. The involvement of the transcription factor HIF-1α was studied by using the specific inhibitor chetomin and its expression was measured by flow cytometry. PEMF exposure induced a time-dependent, HIF-1α-independent release of VEGF from 1321N1 cells. Astrocyte conditioned medium derived from PEMF-exposed astrocytes significantly reduced the oxygen-glucose deprivation-induced cell proliferation and viability decrease in the neuron-like cells SH-SY5Y. These findings contribute to our understanding of PEMFs action in neuropathological conditions and further corroborate their therapeutic potential in cerebral ischemia.